SPEG Interacts with Myotubularin, and Its Deficiency Causes Centronuclear Myopathy with Dilated Cardiomyopathy - Agrawal, Pankaj B.; Pierson, Christopher R.; Joshi, Mugdha; Liu, Xiaoli; Ravenscroft, Gianina; Moghadaszadeh, Behzad; Talabere, Tiffany; Viola, Marissa; Swanson, Lindsay C.; Haliloğlu, Göknur; Talim, Beril; Yau, Kyle S.; et al. (American journal of human genetics, 2014)
Centronuclear myopathies (CNMs) are characterized by muscle weakness and increased numbers of central nuclei within myofibers. X-linked myotubular myopathy, the most common severe form of CNM, is caused by mutations in MTM1, encoding myotubularin (MTM1), a lipid phosphatase. To increase our understanding of MTM1 function, we conducted a yeast two-hybrid screen to identify MTM1-interacting proteins. Striated muscle preferentially expressed protein kinase (SPEG), the product of SPEG complex locus (SPEG), was identified as an MTM1-interacting protein, confirmed by immunoprecipitation and immunofluorescence studies. SPEG knockout has been previously associated with severe dilated cardiomyopathy in a mouse model. Using whole-exome sequencing, we identified three unrelated CNM-affected probands, including two with documented dilated cardiomyopathy, carrying homozygous or compound-heterozygous SPEG mutations. SPEG was markedly reduced or absent in two individuals whose muscle was available for immunofluorescence and immunoblot studies. Examination of muscle samples from Speg-knockout mice revealed an increased frequency of central nuclei, as seen in human subjects. SPEG localizes in a double line, flanking desmin over the Z lines, and is apparently in alignment with the terminal cisternae of the sarcoplasmic reticulum. Examination of human and murine MTM1-deficient muscles revealed similar abnormalities in staining patterns for both desmin and SPEG. Our results suggest that mutations in SPEG, encoding SPEG, cause a CNM phenotype as a result of its interaction with MTM1. SPEG is present in cardiac muscle, where it plays a critical role; therefore, individuals with SPEG mutations additionally present with dilated cardiomyopathy.